2012
DOI: 10.1007/s00330-012-2639-3
|View full text |Cite
|
Sign up to set email alerts
|

IAEA survey of paediatric computed tomography practice in 40 countries in Asia, Europe, Latin America and Africa: procedures and protocols

Abstract: There is significant potential for improvement in CT practice and protocol use for children in less resourced countries. Dose estimates for young children varied widely. This survey provides critical baseline data for ongoing quality improvement efforts by the IAEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 25 publications
2
44
2
2
Order By: Relevance
“…Our survey also found that the DLP values for pediatric CT in Japan were higher than in other surveys [8][9][10][11]. The 75th percentile values of the CTDI vol for pediatric CT in our survey were higher than those in the survey conducted by the IAEA [10].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Our survey also found that the DLP values for pediatric CT in Japan were higher than in other surveys [8][9][10][11]. The 75th percentile values of the CTDI vol for pediatric CT in our survey were higher than those in the survey conducted by the IAEA [10].…”
Section: Discussionsupporting
confidence: 51%
“…All age-based 75th percentiles of the CTDI vol values for the head were 1-2 times higher and DLP values for the head were 0.9-1.9 times higher in the Japanese survey than in the other published surveys. The 75th percentile of the CTDI vol values for the chest were 1.4-3.2 times higher and the DLP values for the chest were 1.4-3.8 times higher in the Japanese survey than those reported from the German, Swiss, Thai and French surveys [7][8][9]11] and nearly equal to the results reported for the British and IAEA surveys [6][7][8][9][10]. The 75th percentile of the CTDI vol values for the abdomen were 1.2-2.4 times higher and the DLP values for the abdomen were 1.1-2 times higher in the Japanese survey than in the German, Swiss, Thai and French surveys [7][8][9]11] and lower than in the British and IAEA surveys [6][7][8][9][10].…”
Section: Displayed Ctdi Vol On Ct Systemsmentioning
confidence: 66%
See 1 more Smart Citation
“…In head CT (Table 9), both CTDI vol and DLP values are comparable with the published data with few exceptions. The results in Table 10 (chest CT) indicate the values in the present study to be higher than the corresponding values from the other studies (10,15) . The differences in the protocols in use and the radiographer's preferences are one of the possible explanations.…”
Section: Comparison With Published Datacontrasting
confidence: 76%
“…However, such potential optimisation may not apply in 'obstruction' environments where even longer screening times can results. The CT procedures were always performed using tube current modulation and paediatric protocols, practices that can reduce dose without compromising with image quality (10,15) . However, further adjusting user-selectable scan parameters such as the use of appropriate scan length, increasing pitch factor and lowering of tube potential can lead to some dose savings.…”
Section: Paediatric Doses During Common X-ray Proceduresmentioning
confidence: 99%